Analisis TAM Terhadap Kepuasan Pelanggan dan Prioritas Perbaikan Aplikasi Maxim dengan IPA (Studi Pelanggan Surabaya) - Cholifah, Ergilia Nur; Iriani, Iriani (Universitas Nahdlatul Ulama Blitar, 2025)
Nowadays maxim is quite attractive to customers in Surabaya, but there are still many customers who complain about maxim application services. The purpose of this study is to analyze TAM on the level of customer satisfaction and priority of improvement in the maxim application study on Surabaya customers. This study uses the IPA method to identify TAM attributes that are priorities for maxim applications to improve first. The results of this study show that maxim application customers in Surabaya City have not been satisfied marked by an average value of 98.98% expectation conformity level.From the quadrant analysis of cartesian diagrams, to improve maxim customer satisfaction in Surabaya City, the company needs to prioritize several aspects, including: establishing partnership relationships with other platforms to integrate new services on the maxim application (AU1), providing customer service that is available 24 hours a day (AU4), updating the user interface to be simpler so that it is easy to understand for various ages (PEOU1), handle customer problems quickly and efficiently (AU3), and provide guidance on how users integrate the features of maxim App in every use of services(AU2).